Aerobic Physical Exercise is Essential for Cardiac Autonomic Regulation in Hypertensive Patients Undergoing Chronic Treatment with Renin- Angiotensin System Inhibitors - de Paula Facioli, Tábata; Philbois, Stella V.; Tank, Jens; Gastaldi, Ada Clarice; Aguilar, Bruno Augusto; da Veiga Oliveira, Ana Catarine; Ferreira, Lucas Dalvit; de Souza, Hugo Celso Dutra (Current Vascular Pharmacology, 2023)
Background: Hypertension treatment with renin-angiotensin system inhibitors (RASi) presents contradictions about the recovery of damage in cardiovascular autonomic modulation characterized by reduced heart rate variability (HRV) and increased blood pressure variability (BPV). Conversely, the association of RASi with physical training can influence achievements in cardiovascular autonomic modulation. Objective: To investigate the effects of aerobic physical training on hemodynamics and cardiovascular autonomic modulation in hypertensive volunteers untreated and treated with RASi. Methods: A non-randomized controlled trial in which 54 men (≅ 40-60 years old) with a history of hypertension for >2 years were allocated in accordance with their characteristics into three groups: untreated (Control; n=16), treated with type 1 angiotensin II (AT1) receptor blocker (losartan; n=21), and treated with angiotensin-converting enzyme inhibitor (enalapril; n=17). All participants underwent hemodynamic, metabolic, and cardiovascular autonomic evaluation using baroreflex sensitivity (BRS) and spectral analysis of HRV and BPV, before and after 16 weeks of supervised aerobic physical training. Results: The volunteers treated with RASi had lower BPV and HRV, both in the supine position and in the tilt test, with the losartan group having the lowest values. Aerobic physical training increased HRV and BRS in all groups. However, the association of enalapril with physical training appears to be more prominent. Conclusion: Long-term treatment with enalapril and losartan may harm the autonomic modulation of HRV and BRS. Aerobic physical training is essential to promote positive adjustments in the autonomic modulation of HRV and BRS in hypertensive patients treated with RASi, especially with enalapril.
Keywords: Hypertension